2020
DOI: 10.1111/jcmm.15339
|View full text |Cite
|
Sign up to set email alerts
|

Classic and targeted anti‐leukaemic agents interfere with the cholesterol biogenesis metagene in acute myeloid leukaemia: Therapeutic implications

Abstract: Despite significant advances in deciphering the molecular landscape of acute myeloid leukaemia (AML), therapeutic outcomes of this haematological malignancy have only modestly improved over the past decades. Drug resistance and disease recurrence almost invariably occur, highlighting the need for a deeper understanding of these processes. While low O 2 compartments, such as bone marrow (BM) niches, are well‐recognized hosts of drug‐resistant leukaemic cells, standard in vitro studies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the cholesterol synthesis of AML cells increased significantly after being exposed to chemotherapy [ 13 ]. Inhibiting cholesterol synthesis can kill AML cells and sensitize them to chemotherapeutic drugs [ 14 , 15 ], suggesting that AML cells require higher levels of cholesterol to maintain survival compared with normal cells and that the imbalance of cholesterol homeostasis may lead to treatment failure. A phase 2 study of pravastatin in combination with idarubicin and cytarabine reported an encouraging response rate for relapsed AML [ 16 ] and improved overall survival for patients in the low-risk group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the cholesterol synthesis of AML cells increased significantly after being exposed to chemotherapy [ 13 ]. Inhibiting cholesterol synthesis can kill AML cells and sensitize them to chemotherapeutic drugs [ 14 , 15 ], suggesting that AML cells require higher levels of cholesterol to maintain survival compared with normal cells and that the imbalance of cholesterol homeostasis may lead to treatment failure. A phase 2 study of pravastatin in combination with idarubicin and cytarabine reported an encouraging response rate for relapsed AML [ 16 ] and improved overall survival for patients in the low-risk group [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blasts were separated as described elsewhere. 38 The clinical characteristics of the patients from whom samples and tissues were derived are listed in Tables 1A and 1B .…”
Section: Methodsmentioning
confidence: 99%
“…Blasts were separated as described elsewhere. 38 The clinical characteristics of the patients from whom samples and tissues were derived are listed in Tables 1A and 1B. Unless otherwise specified, all assays were performed in triplicate and results were obtained in at least three independent experiments.…”
Section: Patient Samplesmentioning
confidence: 99%
“…Cholesterol biosynthesis is transcriptionally induced in AML cells under hypoxic stress conditions and attenuated by cytarabine and quizartinib, the latter being a selective inhibitor of class III receptor tyrosine kinases, including FMS-related tyrosine kinase 3. 37 Interestingly, cytarabine increases intracellular cholesterol content in AML cells independently of O 2 tension, possibly switching to scavenger mode through the upregulation of CD36. In this setting, rosuvastatin exerts a significant antileukemic activity against a wide variety of AML cells and acts synergistically with cytarabine at different levels of O 2 , an observation deserving investigation of rosuvastatin-based therapies to target residual AML cells that reside in low-O 2 environments, such as the leukemic niche.…”
Section: Manipulating Cholesterol Homeostasis In Hematopoietic Malign...mentioning
confidence: 99%